Islamic Republic of Iran : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The Islamic Republic of Iran inherited a highly centralized economy. The state-owned enterprises had monopolies over large sectors of the economy, including the financial system. This was compounded by Iran's excessive dependence on the volatile oil exports. Iran's five-year development plan aims at accelerating growth to create sufficient employment opportunities for a rapidly expanding labor force. De-monopolizing the economy, liberalizing trade, promoting private investment, strengthening the financial system, and improving the fiscal and monetary policy settings is required.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet